PENGARUH KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KOTA DUMAI - Chairuddin Surya Putra; Harlen ' '; Machasin ' ' (Jurnal Ekonomi, 2014)
Based on the background mentioned above, the authors conclude the formulation of the problem, namely: How does the leadership, motivation and organizational culture either partially or simultaneously on employee performance on Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Dumai. The purpose of this study is to analyze done simultaneously and partially Influence Leadership, Motivation and Organizational Culture On Employee Performance Against Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Dumai. This research was conducted at the Office Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Dumai. The population in this study were all employees working in the office Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Dumai. Determination of the number of samples using methods Slovin and obtained a sample of 52 respondents. While the types of data used in this study is primary data and secondary data. Data was collected through interviews and questionnaires. The data analysis method used is descriptive and quantitative methods to sum multiple regression formula. The variables used in this study is X1 (Leadership) with indicators communicate, coordinate, organize, motivate, utilize resources, rewarding, improve the skills of subordinates, the discipline of law, and classifying expectations of the organization. X2 (Motivation) with indicators of working conditions, salary, status, job security, high personal responsibility, willing to take risks, have realistic goals, have a plan of work, using feedback. X3 (Cultural Organization) with indicators of individual initiative, tolerance for risk measures, guidance, integration, management support, control, reward system, tolerance for conflict, communication patterns. Based on the research results, it can be seen leadership significantly influence employee performance on Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Dumai. The better the leadership pattern is applied, the higher the employee's performance. Thus, the presence of leaders in every moment to improve employee performance. Motivation no effect on employee performance. This is due to the motivation of employees are non-material received while an employee is expected motivation of the material. The results showed that the influence of organizational culture on employee performance on Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Dumai. Working culture of individual shaping organizational culture. Of the culture of the organization, can help improve employee performance. Due to a positive organizational culture, may establish a positive working patterns especially in improving employee performance.Kata Kunci : Leadership, Motivation, Organizational Culture and Performance